2022
DOI: 10.3389/fmolb.2022.801478
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Comprehensive Analysis of a circRNA-miRNA-mRNA Regulatory Network to Reveal the Pathogenesis of Hepatocellular Carcinoma

Abstract: Background: Circular RNAs (circRNAs) have been demonstrated to be closely related to the carcinogenesis of human cancer in recent years. However, the molecular mechanism of circRNAs in the pathogenesis of hepatocellular carcinoma (HCC) has not been fully elucidated. We aimed to identify critical circRNAs and explore their potential regulatory network in HCC.Methods: The robust rank aggregation (RRA) algorithm and weighted gene co-expression network analysis (WGCNA) were conducted to unearth the differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…The discovery of circRNA subsets has added a new layer of complexity to the alterations of gene expression associated with epigenetic changes, primarily via the ceRNA network comprised of various circRNA-miRNA-mRNA axes (Shen et al, 2015;Fontemaggi et al, 2021). The dysfunction of circRNA-miRNA-mRNA regulatory signal represents another important epigenetic-controlled mechanism of the pathogenic gene expression in human cancer, which are important nodes in cancer development (Tang et al, 2021;Mo et al, 2022). Mapping the circRNA-miRNA-mRNA network is an important way to elucidate the regulatory role of circRNA being investigated (Rengganaten et al, 2020;Pang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of circRNA subsets has added a new layer of complexity to the alterations of gene expression associated with epigenetic changes, primarily via the ceRNA network comprised of various circRNA-miRNA-mRNA axes (Shen et al, 2015;Fontemaggi et al, 2021). The dysfunction of circRNA-miRNA-mRNA regulatory signal represents another important epigenetic-controlled mechanism of the pathogenic gene expression in human cancer, which are important nodes in cancer development (Tang et al, 2021;Mo et al, 2022). Mapping the circRNA-miRNA-mRNA network is an important way to elucidate the regulatory role of circRNA being investigated (Rengganaten et al, 2020;Pang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA (circRNA) is a type of non-coding RNA with a closed-loop structure that was first discovered in eukaryotes in 1976 [6]. Circular RNAs (circRNAs) have a high expression level, high stability, and tissue specificity [7,8]. They regulate linear RNA transcription and protein translation, performing a variety of different biological functions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, previous studies revealed that circRNAs participate in cancer pathogenesis by sponging miRNAs that target mRNA and circRNAs exhibit potential as predictive biomarkers and therapeutic targets for cancer treatment (5,6). In addition, a previous study demonstrated that circRNA/miRNA/mRNA networks are involved in the development and progression of multiple types of malignancy (7). Results of a meta-analysis demonstrated that nine circRNAs may serve as potential prognostic markers for HNSCC and these are associated with lower overall survival (OS) and poor clinicopathological outcomes in patients with HNSCC (8).…”
Section: Introductionmentioning
confidence: 99%